Whole-transcriptome analyses of Sorghum leaves identify key mRNAs and ncRNAs associated with GA3-mediated alleviation of salt stress - Wu, Yanqing; Liu, Jiao; Zhou, Guisheng (Frontiers in Plant Science, 2022)
Sorghum has recently attracted much attention for its tolerance in high salt environment. However, the effect and regulatory mechanism of the gibberellic acid (GA3)-mediated alleviation of salt stress in sorghum remains unclear. Herein, we reported that a GA3 concentration of 50 mg/L is optimal for sorghum (“Jitian 3”) development under salt stress. We conducted a whole-transcriptome analysis between GA3-treated and control sorghum leaves under salt stress, and we identified 1002 differentially expressed (DE)-messenger RNAs (mRNAs), 81 DE-long non-coding RNAs (lncRNAs), 7 DE-circular RNAs (circRNAs), and 26 DE-microRNA (miRNAs) in sorghum following GA3 treatment. We also identified a majority of DE-mRNAs and non-coding RNAs (ncRNAs) targets that serve essential roles in phenylpropanoid biosynthesis and plant hormone networks. In addition, we generated a competitive endogenous RNA (ceRNA)-miRNA-target gene network, and 3 circRNAs (circRNA_2746, circRNA_6515, circRNA_5622), 4 lncRNAs (XR_002450182.1, XR_002452422.1, XR_002448510.1, XR_002448296.1) and 4 genes (LOC8056546, LOC8062245, LOC8061469, LOC8071960) probably act as valuable candidates for the regulation of the GA3-mediated alleviation of salt stress in sorghum. Our findings uncovered potential mRNA and non-coding RNAs that contribute to GA3 regulation, thus offering a basis for the future investigation of underlying mechanisms of salt stress in sorghum.